Density and diet of invasive alien anuran species in a disturbed landscape: A case in the University of the Philippines Mindanao, Davao City, Philippines - Kublai Januar Jabon; Lief Erikson Gamalo; Mae Responte; Reynaldo Abad; Glenn Dale Gementiza; Marion John Michael Achondo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Jabon KJD, Gamalo LED, Responte MA, Abad RG, Gementiza GDC, Achondo MJMM. 2019. Density and diet of invasive alien anuran species in a disturbed landscape: A case in the University of the Philippines Mindanao, Davao City, Philippines. Biodiversitas 20: 2554-2560. The population density and diet composition of three invasive alien anuran species (IAS) (Kaloula pulchra, Hoplobatrachus rugulosus, and Rhinella marina), recorded from a disturbed landscape in the University of the Philippines Mindanao campus, were determined in this study. With the total area of 18 km2 covered, R. marina (3.89 ind/km2) showed to have the highest density followed by K. pulchra (0.83 ind/km2) then H. rugulosus (0.056 ind/km2). Furthermore, 20 samples of R. marina and 10 samples of K. pulchra were used for gut analysis in which all have stomach contents. Thirteen prey orders were identified in both species with different degrees of prey digestion. The Frequency of Occurrence (FOO) showed orders Spirobolida, Coleoptera, and Hymenoptera were constantly occurring in R. marina while only Hymenoptera for K. pulchra. On the other hand, Degree of Food Preference showed similarities with Hymenoptera as the most preferred prey in both species, especially for K. pulchra (2.8) as compared to R. marina (1.8). Accidental occurrence and occasionally preferred food items such as organic and inorganic matter were also present in both species. A notable record of a skink (Reptilia, Scincidae) as prey item was found in R. marina, indicative of its generalist and carnivorous diet and its potential impact on the native vertebrate fauna in the area. This study proposes that the occurrence of IAS with regards to their high density and variable prey preferences can be a factor disturbing biological diversity in an altered landscape.